Counseling Service Management Overcoming Learning Loss in SMA N 15 Maluku Tengah - La Basaruddin; P. Rahabav; J. Papilaya (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Education enhances human resources, but Indonesian educational institutions face challenges, mainly in management. Effective human resource management involves planning, organizing, directing, and controlling resources. Quality education relies on teachers' classroom management and understanding of student needs. Guidance and counseling are essential, requiring coordination with school programs. The COVID-19 pandemic shifted learning online, highlighting inadequacies in managing counseling services and exacerbating learning loss, especially for students lacking internet access. Addressing learning loss demands comprehensive strategies, including counselor training, technological improvements, and proactive student and parent involvement. This research aims to design an effective counseling program at SMA Negeri 15 Maluku Tengah to address learning loss. In this qualitative research, data analysis involves collecting, simplifying, and presenting relevant information from observations, interviews, and documentation to draw conclusions, ensuring an interactive process aiding in addressing research questions and identified issues. Effective counseling and guidance at SMA Negeri 15 Maluku Tengah require comprehensive planning, involving students and parents to meet students' needs. A well-organized, structured team and regular evaluation are crucial for improving the program, helping students overcome learning loss, enhancing motivation, and achieving better academic performance.